Talking Stick Type Cooperative Learning Model of Students’ Character and Learning Outcomes - Syawal M, Adrian; Wahid, Abdul; Setiawan, Ince Prabu (CV. Eureka Murakabi Abadi, 2025)
The role of education is so important that it does not rule out the possibility of running smoothly without challenges, but rather in its implementation. The study aims to investigate the influence of the application of a realistic approach with the Talking Stick type cooperative learning model on the character and learning outcomes of grade V students. This study used a quantitative approach with a pre-experimental design with a one-group pretest-posttest design. In the Character variable, the F value = 592.361 and Sig. < 0.001, which indicates that the change between pretest and posttest in student character is very significant. In the Learning Outcome variable, the F value = 129.935 and Sig. < 0.001, which also indicates a significant change in student learning outcomes between the pretest and posttest. This can conclude that the realistic approach and the Talking Stick learning model have a significant effect on the character and learning outcomes of students.